2022
DOI: 10.21203/rs.3.rs-1319818/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological characteristics of thoracolumbar fractures from 2014 to 2019 in Shanxi, China

Abstract: Background: We aimed to clarify the epidemiological characteristics of thoracolumbar fractures (TLFs) at Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, China. Methods: A total of 1,096 patients with TLF between January 2014 and December 2019 were included in this retrospective study. Epidemiological characteristics (year, age, sex, marital status, occupation, injury level, etiology, fracture type, and American Spinal Injury Association ASIA impairment scale [AIS] grade) in medical records were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that the proportion of women with thoracolumbar compression fractures is higher than that of men, and is younger than that of men. It tends to occur at the age of 60 ~ 69, while the majority of men are at the age of 70 ~ 79 [4]. The research shows that the incidence of OVCF in China has increased step by step in recent years [5].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Studies have shown that the proportion of women with thoracolumbar compression fractures is higher than that of men, and is younger than that of men. It tends to occur at the age of 60 ~ 69, while the majority of men are at the age of 70 ~ 79 [4]. The research shows that the incidence of OVCF in China has increased step by step in recent years [5].…”
Section: Introductionmentioning
confidence: 83%
“…(1) meet the diagnostic criteria of postmenopausal osteoporosis, TCM syndrome differentiation meets the type of kidney deficiency and blood stasis, and has typical clinical manifestations of osteoporosis; (2) Natural menopause time ≥ 1 year; (3) No anti osteoporosis drug treatment and no drugs affecting bone metabolism have been used in recent 6 months; (4) No other diseases affecting the study, such as endocrine system, digestive system and spirit; (5) No obvious contraindications; (6) Good compliance, with treatment and follow-up; (7) Voluntarily sign relevant informed documents and agree to accept this study.…”
Section: Inclusion Criteriamentioning
confidence: 99%